Towards professionalising Canadian retail management careers: The role of vocational anticipatory socialisation. Issue 3 (27th February 2020) - Gunn, Frances; Cappuccitti, Anna; Lee, Seung Hwan (Mark)
Abstract : Purpose: The purpose of this study is to investigate patterns in the social construction of occupational jurisdiction and related professional career identity. It examines the agency associated with framing messages that influence perceptions about the professional nature and value of retail management careers. The aim is to identify sources which produce influential messages about perceptions about retail management careers and the content of these messages. Design/methodology/approach: This study utilises a qualitative research methodology (focus-group interviews) to explore the observations of people involved with the monitoring and management of career messages. Two focus groups were conducted with a) nine Canadian retail practitioners and b) seven post-secondary educators from retail management education programmes. Findings: The focus groups identify five sources of influential messages including (1) part-time retail work experience, (2) educational institutions, (3) parents, (4) retail industry/practitioners and (5) media. They also identify three content themes presented by these sources including (1) the importance of educational requirements, (2) the nature of occupational roles and (3) the value of the career. Research limitations/implications: The significance and generalisability of the results are limited by the size and nature of the sample. Practical implications: This study makes a practical contribution by identifying potential career awareness strategies. Originality/value: This research makes a theoretical contribution by expanding understanding of the role of communication with career perceptions and with the related constitution of career professionalisation.